Rhodium(III)‐Catalyzed Directed C−H Bond Naphthylation with 7‐Azabenzonorbornadiene as the Naphthylating Reagent. Issue 2 (30th January 2020) - Li, Honghe; Guo, Weicong; Jiang, Jijun; Wang, Jun
Abstract: An efficient rhodium(III)‐catalyzed C−H bond naphthylation reaction is described for the synthesis of diverse anilides and benzamides bearing naphthyl substituents. The substrate scope is broad. The products could be facilely elaborated to various synthetically useful intermediates. To the best of our knowledge, using 7‐azabenzonorbornadienes to achieve naphthylation via transition‐metal‐catalyzed C−H activation has not been reported before. Abstract : Directly to the target ! Rhodium(III)‐catalyzed C−H bond naphthylation reaction has been reported for the synthesis of diverse anilides and benzamides bearing naphthyl substituents. The substrate scope is broad and the products could be facilely elaborated to various synthetically useful intermediates. To the best of our knowledge, using 7‐azabenzonorbornadienes to achieve naphthylation via transition‐metal‐catalyzed C−H activation has not been reported before.